PENINGKATAN LITERASI DAN KEAMANAN DIGITAL MELALUI PROGRAM SOSIALISASI BAGI GENERASI MUDAPENINGKATAN LITERASI DAN KEAMANAN DIGITAL MELALUI PROGRAM SOSIALISASI BAGI GENERASI MUDA - Geisa Affia Zahra; Dian Hartanti; Abyyasanugraha Abyyasanugraha; Sholeh Bayu Anggoro; Jihan Difani; Ahmad Rizki Nurcholis; Ahmad Firdaus; Aditya Yosep; Muhammad Faisyal Akbar; M Rifqi Destian; Aditya Elfan Crisiyo; Ajaduriga Weslov; Agus Setiawan; Bayu Pratama (MAJU : Indonesian Journal of Community Empowerment, 2026)
The rapid development of digital technology has had a significant impact on the lives of adolescents, particularly in the use of social media and digital communication in the school environment. However, the high intensity of digital media use has not been fully balanced by an understanding of digital literacy, language ethics, and awareness of personal data security. Based on these conditions, this community service activity was carried out in Setia Mekar Village, targeting students of SMP Negeri 8 Tambun Selatan. The aim was to improve digital cultural literacy, language politeness, and digital security awareness among students.. The aim was to improve digital cultural literacy, language politeness, and digital security awareness among students. The implementation methods included educational counseling, interactive discussions, and simple simulations related to social media ethics, hoax recognition, and personal data protection. The results of the activity showed an increase in students' understanding of the importance of communicating politely in the digital space, being wise in filtering information, and being more aware of digital security risks. This activity is expected to contribute to shaping the character of students who are intelligent, ethical, and responsible in facing the challenges of the digital world.